Identity and Autobiography in Ambiguous Adventure and Go Tell It on the Mountain - M'Baye, Babacar (Revista Língua&Literatura, 2012)
Although they evolve out of separate parts of the Atlantic Ocean, James Baldwin’s Go Tell It on the Mountain (1953) and Cheikh Hamidou Kane’s Ambiguous Adventure (1961) are two similar autobiographical novels that examine parallel dilemma of people of African descent who attempt to overcome the dualities and other quagmires that racial and colonial oppressions have created in their lives and in their relationships with modernity and traditions. Yet the two novels do not dwell in pessimism since they suggest the remarkable ways in which people of African descent rise from the predicament and schism of racial and colonial dominations in order to create viable notions of modernity that help them establish a neat balance between the traditions of their ancestors and those of the Europeans that either alienated or tyrannized them. Coming from such adversity, Blacks of Africa and the Diaspora are able to reconstruct their lives, maintain their sanity, and envision a world of infinite possibilities.